1999
DOI: 10.1300/j013v29n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence in Working Women: An Exploratory Study

Abstract: Women who work for a large academic center were surveyed about urinary incontinence. The response rate was 57%. Of the 1113 usable questionnaires, 232 (21%) indicated that urinary incontinence occurred at least monthly. The average age of incontinent women was 45 years (SD = 10 years). Incontinent women were significantly older and had a higher body mass index than continent women. There were also ethnic differences between incontinent and continent groups, although ethnicity was not a predictor of incontinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 45 publications
8
29
0
6
Order By: Relevance
“…This result was consistent with other investigations that found prevalence of 21% (9) and 29% (10) among workingwomen. Thirty-two percent of the participants in the present study complained that UI imposed some kind of restriction on their lifestyle, mainly concerning occupational and sexual activities.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result was consistent with other investigations that found prevalence of 21% (9) and 29% (10) among workingwomen. Thirty-two percent of the participants in the present study complained that UI imposed some kind of restriction on their lifestyle, mainly concerning occupational and sexual activities.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that between 26.3% and 51.9% of young women from 19.9 to 32.2 years of age reported urine loss while participating in sport or exercise practice (4,(6)(7)(8) . Even among working women who do not perform activities that require greater physical exertion, with ages equal to or lower than 50 years, UI presented prevalence indices of 25% (9,10) . It was observed in the literature that there are no studies concerning nursing professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado mostrou consistência com outros estudos que encontraram prevalência de 21% (8) e 29% (9) entre mulheres trabalhadoras.…”
Section: Discussionunclassified
“…A exposição diária da condição de incontinência perante os colegas de trabalho causou estresse, vergonha, constrangimento, prejudicando a concentração e o desempenho. O impacto da IU na atividade ocupacional foi semelhante aos estudos com mulheres que exerciam diferentes atividades ocupacionais (8,9) , assim como, naquelas que realizavam maior esforço físico (12) .…”
Section: Discussionunclassified
See 1 more Smart Citation